KOMBINASI TEKNIK MULLIGAN DAN FASILITASI VASUS MEDIALIS OBLIQUUS LEBIH EFEKTIF MENINGKATKAN AKTIVITAS FUNGSIONAL DARIPADA APLIKASI KINESIO TAPING PADA SINDROMA NYERI SENDI PATELLOFEMORAL - Yulianti, Atika; Tirtayasa, Ketut; -, Sugijanto (Sport and Fitness Journal, 2013)
Patellofemoral pain syndrome is complained of knee pain by young adults who are productive oftenly, syndrome characterized by pain that is felt around the kneecap, and aggravated the activity squat and stand, up and down stairs, and change the position of the knee after a long standstill ( stand up after sitting for a long time). This is due to the weakness of the thigh muscles especially vasus medialis obliquus . Reinforcement of weak muscle in particular strengthening of the vastus medialis  oblique an appropriate treatment to increase the functional activity of the syndrome. The study was a randomized experiment with pre and post-test group design. This study aimed to compare the combining of mulligan techniques and facilitate of vasus medialis obliquus with application of kinesio taping to increase the functional activity of the lower extremities. In this study, 11 respondents were given a combination of mulligan techniques and facilitation of vastus medialis oblique for 5 weeks with a frequency of exercise 3 times a week, and 11 respondents provided application of kinesio taping for 5 weeks with 3 days and replaced with a new taping. Each treatment was measured by the Lower Extremity Fungtional Scale before and after 5 weeks. Statistical analysis parametric paired sample t-test results is the influence of a combining of mulligan techniques and facilitate of vastus medialis oblique and application of kinesio taping to increase the functional activity of the lower extremities with p<0.05. Test of different with the independent sample t-test with a result there are significant difference between the combining of techniques mulligan and facilitation of vasus medialis obliquus with application of kinesio taping values with  p <0.05. Conclusions in this study that a combining of mulligan techniques and facilitation of vasus medialis obliquus , 3 times a week for 5 weeks effectively to increase the functional activity of the lower extremities of patients with patellofemoral pain syndrome compared to application of kinesio taping for 5 weeks with 3 days in a single use.
Keywords: mulligan techniques, facilitation of vastus medialis oblique, kinesio taping, patellofemoral